Characterizing a Cohort of α-Thalassemia Couples Collected During Screening for Hemoglobinopathies: 14 Years of an Iranian Experience. (June 2014) - Hafezi-Nejad, Nima; Khosravi, Mohsen; Bayat, Nooshin; Kariminejad, Ariana; Hadavi, Valeh; Oberkanins, Christian; Azarkeivan, Azita; Najmabadi, Hossein
Abstract Our study aimed to determine the number of couples with normal hemoglobin (Hb) electrophoresis and low-borderline hematological values, which may come up with a clinically critical status in their offspring. The number of couples at risk for severe α-thalassemia (α-thal) needed to be estimated before recommending genetic counseling and prenatal diagnosis (PND). During the past 14 years, from at least 7000 referrals, 754 couples were investigated for α-thal by direct mutation detection methods followed by reverse strip assay and α-globin gene sequencing for inconclusive cases. Detection of silent β-thalassemia (β-thal) mutations was done in suspected cases by complete β-globin gene sequencing. We were able to provide a molecular diagnosis in 87.3% (658/754) of couples. A total of 9.1% (60/658) may have a clinically significant hemoglobinopathy in their offspring. Significant conditions included hydrops fetalis (20.0%; 12/60), certain Hb H (β4) genotypes (78.3%; 47/60) and β-thal intermedia (β-TI) (1.7%; 1/60). The diagnostic flowchart for couples with microcytic hypochromic anemia in countries with a high prevalence of hemoglobinopathies should include α and β gene sequencing. As our results indicate, every nine out of 100 of these couples will face significant hemoglobinopathies and every two out of 100 can carry Hb Bart's (γ4) hydrops fetalis in their pregnancies. For such cases, PND should be utilized to allow the carrier couples to decide whether or not to abort the fetus.